PENERAPAN SNI 2847-2019 DAN SNI 8460-2017 PADA PEKERJAAN TULANGAN PENJANGKARAN PONDASI DALAM PADA PILECAP - Prijasambada, Prijasambada (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2025)
SNI 2847-2019 has been in effect for six years, and SNI 8460-2017 has been in effect for eight years since its enactment. However, in practice, some aspects of these SNIs have not been properly implemented in structural projects, both in government and private sectors. This study aims to determine the extent to which these regulations have been implemented. The study wasconducted in several projects across Indonesia, both in government and private sectors. The study focused on the application of anchorage lengths for deep foundation reinforcement, both for piles and bored piles, within pile caps. The results revealed that most projects still do not implement established SNI standards. This issue should be a concern for all parties involved in project planning, including planning consultants, management consultants, contractors, and project owners.